2018
DOI: 10.2147/dmso.s145862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aerobic exercise on echocardiographic epicardial adipose tissue thickness in overweight individuals

Abstract: BackgroundEpicardial adipose tissue thickness (EATT) measured by echocardiography is a reliable indicator of visceral adipose tissue in the body and metabolic syndrome. The objective of this work was to study the effect of 12-week aerobic exercise training on echocardiographic epicardial adipose tissue thickness (EEATT), body composition and other metabolic parameters in asymptomatic overweight adults.MethodsA total of 170 overweight and mild obese individuals were randomly allocated to 12-week aerobic exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
1
20
0
1
Order By: Relevance
“…Moreover, Şeker et al [25] reported that epicardial adipose tissue thickness was independently associated with abnormal LV geometry, hypertrophy, and dysfunction, as well as low-grade chronic inflammation. A study by Bairapareddy et al [26] showed that EAT correlated with VAT, so we can assume that results by Şeker et al [25] indirectly corroborate our observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, Şeker et al [25] reported that epicardial adipose tissue thickness was independently associated with abnormal LV geometry, hypertrophy, and dysfunction, as well as low-grade chronic inflammation. A study by Bairapareddy et al [26] showed that EAT correlated with VAT, so we can assume that results by Şeker et al [25] indirectly corroborate our observations.…”
Section: Discussionsupporting
confidence: 91%
“…These last observations may be explained by the above-mentioned data concerning the effect of adiposity (FM, VAT and EAT) on heart remodelling [7,25]. The influence is related to a direct paracrine effect of EAT, the thickness of which correlates with visceral adiposity, as well as the endocrine and proinflammatory activity of VAT [10][11][12]26]. The results of this study have some limitations.…”
Section: Discussionmentioning
confidence: 85%
“…All were conducted in individuals who had, on average, overweight or obesity (body mass index >25 kgÁm −2 ), with mean age ranging from 23 to 68 years. However, other participants' characteristics differed across studies, with four of them specifically conducted in individuals with overweight or obesity, [27][28][29]31 two in individuals with metabolic syndrome, 23,30 one in individuals with high CVD risk (e.g., Framingham 10-year risk score >20%), 24 one in patients on hemodialysis, 22 one in individuals with depressive disorders, 26 and one combining people who were healthy and individuals with defective glucose tolerance. 25 Exercise interventions were supervised in all cases and included three sessions per week ($30-60 min per session) in the majority of cases except for one study, in which training frequency was not specified.…”
Section: Studies' Characteristicsmentioning
confidence: 99%
“…24 However, other characteristics such as length of the intervention (which lasted between 2 and 16 weeks) differed considerably between studies. Moreover, studies included different types of ET, moderate-intensity continuous (MICT) 22,24,26,29,30 or high-intensity interval training (HIIT), 23,25,31 or RT interventions (e.g., circuit of seven to 10 exercises with three to five sets of $10 repetitions), 27,28,31 and one study also assessed the effects of exergaming (i.e., exercising [in this case running and jumping] while playing a video game). 24 None of the studies reported any adverse event related to the exercise interventions (e.g., no musculoskeletal injury).…”
Section: Studies' Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation